2019
DOI: 10.1016/j.celrep.2019.02.097
|View full text |Cite
|
Sign up to set email alerts
|

Prdm12 Directs Nociceptive Sensory Neuron Development by Regulating the Expression of the NGF Receptor TrkA

Abstract: Highlights d In somatosensory ganglia, Prdm12 is specific to the nociceptive lineage d Prdm12 is necessary for the survival of developing nociceptors d Prdm12 initiates and maintains the expression of TrkA in developing nociceptors d Prdm12 acts in conjunction with bHLH proteins Ngn1/2 to promote a nociceptor fate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
92
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 76 publications
(131 reference statements)
11
92
2
Order By: Relevance
“…It is highly conserved from mouse to human, with 98% protein identity, suggesting a highly conserved function, and opening the gateway for study in mouse models. Indeed, consistent with the idea of having a highly conserved function, loss-of-function of PRDM12 in humans or its homologs in Drosophila, frog embryos, and mice leads to abnormalities in sensory neuron development (Bartesaghi et al, 2019;Chen et al, 2015;Desiderio et al, 2019;Moore et al, 2004;Nagy et al, 2015). Additionally, Prdm12 is specifically expressed in myelinated Aδand unmyelinated C-fiber nociceptors into adulthood (Chen et al, 2015;Kinameri et al, 2008;Nagy et al, 2015;Sharma et al, 2020;Thelie et al, 2015;Usoskin et al, 2014).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…It is highly conserved from mouse to human, with 98% protein identity, suggesting a highly conserved function, and opening the gateway for study in mouse models. Indeed, consistent with the idea of having a highly conserved function, loss-of-function of PRDM12 in humans or its homologs in Drosophila, frog embryos, and mice leads to abnormalities in sensory neuron development (Bartesaghi et al, 2019;Chen et al, 2015;Desiderio et al, 2019;Moore et al, 2004;Nagy et al, 2015). Additionally, Prdm12 is specifically expressed in myelinated Aδand unmyelinated C-fiber nociceptors into adulthood (Chen et al, 2015;Kinameri et al, 2008;Nagy et al, 2015;Sharma et al, 2020;Thelie et al, 2015;Usoskin et al, 2014).…”
Section: Introductionsupporting
confidence: 52%
“…Early reports indicated that PRDM12 promoted expression of sensory neuronal markers (Kinameri et al, 2008;Matsukawa et al, 2015;Thelie et al, 2015;Yang and Shinkai, 2013). Consistent with this, Prdm12 was found to be necessary for the initiation and maintenance of tropomyosin receptor kinase A (TRKA) expression, a marker for early nociceptor development (Desiderio et al, 2019). In addition, in the absence of Prdm12, the entire nociceptor lineage failed to develop.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…To differentiate hESCs to sensory neurons, we used a previously described protocol (Chambers et al, ; Desiderio et al, ; Young et al, ). Briefly, neuronal differentiation protocol is executed in different phases, starting with the formation of neurectoderm (Chambers et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…2a, h, i). Both factors play an important role in lineage specification in the developing spinal cord [32][33][34] . However, whether these factors play a similar role in the hypothalamus has not been studied.…”
mentioning
confidence: 99%